Front Cover: Selective and Scalable Electrosynthesis of 2H‐2‐(Aryl)‐benzo[d]‐1, 2, 3‐triazoles and Their N‐Oxides by Using Leaded Bronze Cathodes (Chem. Eur. J. 25/2020). Issue 25 (28th April 2020) - Wirtanen, Tom; Rodrigo, Eduardo; Waldvogel, Siegfried R.
Abstract : Electroreductive synthesis of 2H‐ 2‐(phenyl)benzo[ d ]‐1, 2, 3‐triazole and its N‐oxide from 2‐nitroazobenzene is portrayed in the cover artwork. The electrolytic conversion can selectively stop on the intermediate or final target compound, controlled by the amount of charge applied. The scalable electrosynthesis is run on the simplest electrochemical setup: constant current is applied between two electrodes in an undivided cell. More information can be found in the Communication by S. R. Waldvogel et al. on page 5592 .